Dental care for persons with disabilities: discretion on the frontline - Joana Danielle Brandão Carneiro; Ana Paula Chancharulo de Moraes Pereira; Aylene Bousquat; Paulo Frazão (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To depict the influence of discretionary actions exercised by frontline professionals and organizations on the implementation of diverse modalities of access to specialized dental care within the Care Network for Persons with Disabilities. METHODS A case study conducted in two Brazilian health regions characterized by distinct means of access to specialized dental care employing documentary analysis and interviews with key stakeholders across the period spanning from July to December 2019. RESULTS In the referenced access region, there was a notable centrality of Primary Health Care (PHC) in caregiving, wherein planning and assessment were integral components of institutional routines. Where spontaneous demand scheduling was accepted, sporadic exchanges of information were evident between PHC units and specialized facilities. The coordination role in caregiving was not vested in PHC teams, and activities such as planning and assessment were not assimilated into organizational routines. CONCLUSIONS The implementation of policies for specialized dental care for persons with disabilities relied on the coordination furnished by PHC and the orchestration of planning and assessment endeavors aimed at establishing an integrated care network. This implementation proved subject to the discretionary authority of frontline professionals and organizations, highlighting the significant role of relational and institutional environments in the context of public policy implementation within a decentralized and regionalized healthcare system.